Development of new types of bolted joints for cold-formed steel moment frame buildings. (1st June 2022) - Yin, Lingfeng; Niu, Yu; Quan, Guan; Gao, Han; Ye, Jun
Abstract: It has been a growing trend to use cold-formed steel (CFS) sections as primary structural members in low to multi-story buildings due to their high strength-to-weight ratios, ease of construction and flexibility in manufacturing to a variety of cross-sectional shapes. However, CFS frames are not widely used in seismic regions; one important reason is that the less redundant CFS joints generally have low ductility and energy dissipation capacity due to their inherently thin-walled properties. To address this issue, this paper presents an experimental programme and the corresponding results on two types of beam-to-column CFS joints, which are assembled to the two adjacent surfaces of the built-up CFS column in this paper. Different from the previous research, the two types of joints proposed are potentially suitable to connect CFS members in T-, L- and cruciform joints for multi-story framed-structure buildings. It was observed from the tests that the beams buckled before the occurrence of obvious damage to the tested joints. The two types of joints satisfied the seismic design philosophy of 'strong connection-weak beam'. Joint Type 2 (JT2) exhibits overall higher performance in terms of strength, ductility, and energy dissipation capacity than the Joint Type 1 (JT1). JT1 satisfies the rotational requirement for Ordinary Moment Frames (OMFs) while JT2 satisfies the rotational requirement for Special Moment Frames (SMFs), as defined in AISC Seismic Provisions. The connection zones within both joints can be classified as semi-rigid according to the approach recommended by Eurocode 3: Part 1–8, with JT1 exhibiting higher stiffness than JT2. Overall, the proposed two joints connected with very slender beams and less bolts, have so far shown moderate performance to provide resistance and ductility to be applied in CFS framed buildings in seismic regions, which can be improved in further work. Highlights: New types of joints proposed for moment resisting frames. Tests conducted to investigate the structural behaviours under cyclic loading. Joints provided good strength, stiffness and energy dissipation capacity. Local buckling of beams postponed due to the well designed connection. Joints satisfied the design philosophy of 'strong-connection weak-beam'.